Penerapan Trainer Seri Paralel Bagi Siswa SD Pojok Kota Kediri - Indrawati, Elsanda Merita; Suwardono, Agus; Sari, Kartika Rahayu Tri Prasetyo; Manikta, M. Dewi; Maulidina, Miftakhul; Prahesti, Fidya Eka; Kamelia, Riza; Jalil A, Moh. Abd. (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Abstract—Paralel series circuit thematic material is one of the materials that is difficult for elementary school (SD) students to understand because it requires direct understanding and application of paralel series material. At SD Negeri Pojok Kota Kediri the paralel series material is taught in class VI, the lack of learning media for this material causes students to have difficulty understanding the material. The aim of this Community Service (PkM) activity is to design and implement a paralel series trainer for elementary school students so that it is hoped that students will find it easy to understand and apply the series. This service activity produced 4 trainers, namely a series circuit trainer, a paralel circuit trainer, a combination switch circuit trainer, and a paralel series resistance interactive trainer. The results of applying the trainer show that 90% of students are able to apply circuits to series and paralel material using the series paralel circuit trainer.